Peranan Lembaga Adat dalam Pelaksanaan Pembangunanan di Desa Balla Barat Kecamatan Balla Kabupaten Mamasa - Kristin Natalia (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2019)
This research aims to find out how the traditional institute of Balla west village in collecting and channeling aspirations to the developing community, as well as to know how customary institutions in improving activities in Balla West Village, Balla District, Mamasa Regency.The research method used is qualitative method with descriptive type. Data collection using literature study techniques, and interviews. Furthermore, the data are analyzed qualitatively. The results of this study indicate that first, the role of traditional institute in Balla west village in accommodating and channeling the aspirations of the community has not been implemented properly, it is seen from the parties responsible. The suggestions provided by the traditional institute can not be used well by the public in collecting information and responses, since they are inaccessible to all communities. As well as the traditional institute also does not schedule the right time to hold a joint meeting. Secondly, the role of the traditional institute in increasing community participation in this case does not exist, it is seen that the traditional institute in Balla west village are not proactive towards physical development. The program of physical development in Balla west village on the third party is transferred to an institution formed from the traditional institute.